Combas & Co. or the Figure and the Great Divide - Monique Yaari (Studies in 20th & 21st Century Literature, 1996)
The young painter, Robert Combas, leader of the 1980s "figuration libre" 'free figuration' movement, is seen here both as representative of stylistic and thematic trends in contemporary French art, and as illustrative, through the unfolding of his career, of the object "painting" and its sociology in contemporary France. Examined are: first, the "Postmodern convergence" of figurative, indeed narrative art, with the collapse of the "great divide" between elite and popular art forms; and second, traits such as hypertrophic verbal paratext, high erotic content, and political stand. Similar threads are followed in the work of a number of other artists, old and young, established or not, female and male—hence the "& Co." of the title. The essay raises, without claiming to solve, a set of sociologically and politically informed questions: What forces have shaped Combas' sensibility and style? What forces have made him a minor celebrity domestically, one that France's awesome cultural apparatus considers worthy of export? What, in the formation of contemporary mentalities and tastes, may account for the parallels found among artists as diverse as Combas, Quardon, Pierre and Gilles, Ben, and Klossowski?
Keywords: Robert Combas; figuration libre; contemporary French art; narrative art; hypertrophic verbal paratext; erotic; erotic content; politics; collaboration; Quardon; Pierre; Gilles; Ben; Klossowski